The impact of manufactured sand (M-Sand) as partially and fully replacement of fine aggregate in concrete - Nadimalla, Altamashuddinkhan; Masjuki, Siti Aliyyah; Saad, Siti Asmahani; Lee Woen, Ean; Ali, Maisarah; Ulla, Naseer (ASTES Publishers, 2020)
This, research work was to study the potential of M-sand as compared to river sand in concrete, here M-sand is replaced by river sand 0%,45%,50%,55% and 100% in the concrete mix, Mix design is designed as per IS Standards. In this research a mix 1:2.32:2.82 (M20) was considered. The test specimen was casted for 7days, 28 days and 90days. The performance of M-sand was determined by several experiments such as slump test, impact strength test, flexural Strength, and compressive strength test. The results attained from each test states that as M-sand increases the slump value decreases. flexural strength, compressive strength and impact test of concrete at 7 days, 28 days and 90 days is greater at 100% and 50% replacement of M sand by river sand.